2021
DOI: 10.3389/fimmu.2021.755995
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of IL-2 to the T Cell Surface Through Phosphatidylserine Permits Robust Expansion of CD8 T Cells

Abstract: The phospholipid phosphatidylserine (PS) is naturally maintained on the cytoplasmic side of the plasma membrane. Independent of apoptosis, PS is redistributed to the surface of CD8 T cells in response to TCR-mediated activation. Annexin V (AnnV) is a protein known to bind PS with high affinity and has been effectively utilized to anchor antigen to the surface of CD8 T cells. To expand these studies, we aimed to exploit TCR activation driven PS exposure as a target to deliver cytokine, namely interleukin-2 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…A strategy relying on TP8 to enhance TRAIL resistance properties appears to be feasible, but the study did not clarify whether TP8 targets tumor tissues. Another study showed that the fusion protein ANV-IL2 was more effective in enhancing T-cell activation than recombinant IL-2 because interleukin-2 (IL-2) carrying ANV could deliver IL-2 to the surface of CD8 T cells where transient rearrangement of phospholipids occurred [ 34 ]. This finding suggests that the ANV fusion protein is an effective way to target PS, and, with the help of the high affinity of ANV for PS, ANV could play a role in tumor therapy as well as in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…A strategy relying on TP8 to enhance TRAIL resistance properties appears to be feasible, but the study did not clarify whether TP8 targets tumor tissues. Another study showed that the fusion protein ANV-IL2 was more effective in enhancing T-cell activation than recombinant IL-2 because interleukin-2 (IL-2) carrying ANV could deliver IL-2 to the surface of CD8 T cells where transient rearrangement of phospholipids occurred [ 34 ]. This finding suggests that the ANV fusion protein is an effective way to target PS, and, with the help of the high affinity of ANV for PS, ANV could play a role in tumor therapy as well as in the immune response.…”
Section: Discussionmentioning
confidence: 99%